Saberes e sabores na comunidade quilombola de Lagoa Grande em Feira de Santana-Ba: a alimenta??o como s?mbolo de identidade cultural - Rocha, Paloma Josefa dos Santos (2024)
This research was developed in the quilombola community of Lagoa Grande, whose general objective was to understand how quilombola food, experienced in quilombola communities in Feira de Santana- BA, occurs and can contribute to educational processes in the practice of food production with the reaffirmation of cultural and ancestral identity. As specific objectives we have: characterize the knowledge and food practices used in Quilombola Communities; understand how the memory of subjects in their eating practices relates to traditional and ancestral knowledge; evaluate the socio-environmental and cultural aspects related to quilombola food in the Quilombola Community of Lagoa Grande. This research was qualitative, of an ethnographic nature, the data was collected through individual conversations that were carried out with five participants, as well as using observation as a research instrument. In this way, quilombola food takes place in the Lagoa Grande environment through the ancestral knowledge of these people, collective memories, the sharing of knowledge and orality present among its residents, since all quilombola wisdom is transmitted from person to person, mainly from older to younger. Furthermore, the community consumes, plants and sells quality food, without the use of pesticides, but they also use food from other cultures on a daily basis.